Viabilidade de formação de redes espontâneas pessoais de conhecimentos entre docentes de pós-graduação das áreas de Ciência da Informação e Administração da UFPB - Moreno, Danielle Harlene da Silva (2010)
It deals with information and knowledge as key assets within the organizations, and the prospect of Information Science investigates the properties and behavior of information, the forces that govern the information flow and processing facilities. From this perspective, the objective is to analyze the feasibility of collaborative networks of spontaneous internal personal knowledge between teachers / actors programs Graduate in Business Administration (PPGA) with teachers / actors within the management of the Post Graduate Information Science (PPGCI) UFPB. The choice of search field is on the Programs Graduate Administration and Information Science located at the CCSA / UFPB whose subjects are the teachers of the permanent program. It takes as a tool for data collection curriculum lattes site CNPq. These data were supplemented and annotated in previously created form that includes the following information: name, qualification (undergraduate and graduate) courses taught in graduate school, a research group that works thematically (dissertation and thesis), guidance (graduate). Based on the analysis and interpretation of results, it appears that is appropriate to propose the cooperation networks for the spontaneous sharing of knowledge like that can be applied to the development of programs Postgraduate (PPGA and PPGCI), motivated by learning, where we can look for partnerships, to foster relationships through the promotion of events to promote meeting to present projects and research in progress in both programs Graduate, intensify calls for teachers to give lectures in rooms class in each subject correlated with their area and others.